Extended reality as a means to enhance public health education - Lee, Ying-Chiang Jeffrey; Takenaka, Bryce Puesta (Frontiers in Public Health, 2022)
Technology has transformed the classroom and learning environments. From electronic whiteboards to tablet computers, educators now have access to a multitude of tools that enhance the learning experience. Educational technologies that rely on extended reality (XR) such as augmented and virtual reality are being used, or suggested for use, in various settings and often focus on technical fields such as medicine, dentistry, and aviation. Here, we propose that XR can be used in public health education to better prepare both undergraduate and graduate trainees for real world, complex public health scenarios that require public engagement, investigative skills, and critical decision making. Several opportunities for XR use are outlined that provide perspective on how XR can supplement traditional classroom instruction methods by providing an immersive, participatory training environment. XR offers an opportunity for public health students to gain confidence, have repeated simulated exposures in a safe and equitable environment, and build competency in critical functions they will likely perform as future public health professionals.